Diagnostic dilemma for an unusual presentation of thyroid malignancy - Riju, Jeyashanth (Indian Journal of Case Reports, 2018)
Diagnosis is a crucial element for prompt identification and treatment of serious diseases. Thyroid malignancy presenting as brain metastasis is a rare entity while presenting as colon metastasis is extremely rare. Here, we discuss the difficulty faced with the diagnosis of the same. We report the case of a 66-year-old male, who was a known diabetic and hypertensive and presented with the complaint of the right facial nerve weakness. On evaluation, he was found to have an extradural lesion in the right petrous bone. He underwent pre/retrosigmoid craniotomy and subtotal decompression of lesion. Histopathology showed metastatic adenocarcinoma. He underwent positron emission tomography/computed tomography scan, which showed metabolically active foci in the posterior cranial fossa, ascending colon, manubrium sterni, and lung. Colonoscopy demonstrated a polyp in the ascending colon, biopsy of which revealed metastasis from the thyroid. Later, he was found to have a nodule of 1 cm in the right lobe of thyroid. Total thyroidectomy was done and the histopathology showed a multifocal papillary carcinoma thyroid follicular variant with tall cell areas and capsular invasion.